Stories of a life afield : "Brothers in arms" and "Thanks to Gert" - Smith, A. Hunter (The University of South Carolina Press, 2014)
Two short stories about the life lessons a hunter learned in pursuit of wild turkeys and deer. In "Thanks to Gert," the first of this two-story eBook, A. Hunter Smith recalls one of the funniest and most productive April turkey-hunting seasons he has experienced in the 35 years he has spent in pursuit of one of God's most maddening, frustrating, and divinely conceived creations. "Brothers in Arms" is a story about hunters and fishermen who discover that their best teachers are the wild creatures they hunt. Elders and mentors may impart advice, but Smith has learned the inescapable rules of hunting by observing the actions of the wild things around him. These rules, Smith says, equalize us all in the struggle of life and death in the natural world.